Leptin gene polymorphism affects leptin level in childhood asthma - Szczepankiewicz, Dawid (World J Pediatr, 2018)
BACKGROUND: Leptin may induce inflammation in asthma by activation of Th2 cells. It has also been demonstrated that leptin expression increases upon inflammation and that asthmatic patients show increased serum leptin levels. We hypothesized that the polymorphism in leptin (LEP) and leptin receptor (LEPR) genes is associated with childhood asthma and may affect their serum level. To our knowledge, there are no reports analyzing LEP and LEPR polymorphisms in association with their serum levels in childhood asthma. METHODS: We analyzed 35 subjects: 25 asthmatic pediatric patients and 10 healthy children aged from 6 to 18. The diagnosis of allergic asthma was based on clinical manifestation, lung function, positive skin prick tests and increased immunoglobulin E levels. The polymorphisms were genotyped with use of polymerase chain reaction-restriction fragment length polymorphism method. Serum levels of leptin and leptin receptor were determined using BioVendor enzyme-linked immunosorbent assay kits. Statistical analysis was done with Statistica v.12. RESULTS: We observed that leptin levels were increased in asthmatic subjects as compared to healthy controls and were significantly higher during exacerbation than in the asymptomatic period (P = 0.025). We observed that LEP polymorphism (rs13228377) was associated with higher serum leptin levels in asthma and these two variables had high predictive value for asthma risk (P = 0.007, odds ratio 17.5, predictive accuracy 83.9%). LEPR polymorphisms did not show association with its serum level and asthma risk. CONCLUSION: LEP polymorphism may increase asthma risk via influence on its serum level.